Oxford, the Collegiate University Conflict, Consensus and Continuity - Tapper, Ted.; Palfreyman, David; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Oxford is one of the world$1 (Bs great universities but this has not meant that it is exempt from pressures for change. On various fronts it has been required to meet the challenges that universities almost worldwide have to face. Given the retrenchment of public funding, especially to support undergraduate teaching, it has been required to augment its financial base, while at the same time deciding how to respond to pressure from successive governments determined to use higher education to achieve their own policy goals. While still consistently ranked as a world-class university, it has to decide how it is to acquire the funding to continue in this league, or whether this goal is worth pursuing. Oxford is a collegiate university, which means its colleges share with the University responsibility for the delivery of its central goals. Is this balance of authority shifting over time? If so, how is this to be accounted for, and what are the likely outcomes for the collegiate university? This book sets out to address these questions and arrives at an essentially positive conclusion. Oxford will continue to remain an effective collegiate university and, while its identity will change, its central character will persist.s
Foreword -- Preface -- 1. Setting the Context: Oxford$1 (Bs Changing Academic and Social Demography -- 2. Collegiality Debated -- 3. Continuity and Change in the Collegiate Tradition -- 4. Commensality: Time and Space, Port and Sport, Code and Dress -- 5. The Elusive Search for the Best and the Brightest -- 6. The Tutorial System: The Jewel in the Crown -- 7. Governance: A Community of Self-Governing Scholars? -- 8. Finance: The Well-Endowed Corporation? -- 9. The Collegiate University in Retreat? -- Postscript: What Future for the Collegiate University? -- Appendix: Interviewees -- References -- Index.s
Keywords: Education; Education, Higher; Education; Higher Education; Educational Policy and Politics; International and Comparative Education; Administration, Organization and Leadership